The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1080/00288233.2003.9513542
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of atrazine and phosphate as affected by soil depth in allophanic and non‐allophanic soils

Abstract: Quantification of soil processes, such as adsorption, is needed for predicting the fate of agricultural chemicals in soils. Adsorption is affected by soil properties, which vary with depth. We conducted a laboratory study to determine the influence of soil depth on the adsorption of an organic solute (atrazine) in both allophanic and non-allophanic soils, and an inorganic solute (phosphate) in two non-allophanic soils. Adsorption isotherms of atrazine and phosphate were determined using 14 C-labelled atrazine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
3
1
Order By: Relevance
“…It was suggested that the clay content of the soil strongly affected adsorption of E. coli. Clay particles have also been reported as being influential on the adsorption of agricultural contaminants such as, for example, phosphates (Magesan et al 2003). As the ≤2 μm fraction could not be investigated in this study, it may be that a significant proportion of cells were associated with the 1-2 μm clay fraction of Rowden soil and this would explain the deficit between the results in this study and that of Ling et al (2002).…”
Section: Discussioncontrasting
confidence: 79%
“…It was suggested that the clay content of the soil strongly affected adsorption of E. coli. Clay particles have also been reported as being influential on the adsorption of agricultural contaminants such as, for example, phosphates (Magesan et al 2003). As the ≤2 μm fraction could not be investigated in this study, it may be that a significant proportion of cells were associated with the 1-2 μm clay fraction of Rowden soil and this would explain the deficit between the results in this study and that of Ling et al (2002).…”
Section: Discussioncontrasting
confidence: 79%
“…The K f value obtained in our work better agrees with the data for volcanic soils of New Zealand. For example, Baskaran et al [9] reported K f = 3.74 cm 3 /g averaged for 10 volcanic soils; Magesan et al [36] obtained K f values in the range 0.72-8.79 cm 3 /g for six depths studied.…”
Section: Resultsmentioning
confidence: 96%
“…(3) ( Table 2) was slightly underestimated. For volcanic soils of New Zealand, its values vary in the range of 0.89-1.13 [36]. The variation range of this parameter in Andosols is unknown, because no estimated or experimental val ues are available for it in the literature.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Although adsorption-desorption of atrazine (Atz) in subsurface sediments is generally low, but, there is sufficient retention to warrant consideration of sorption processes in the assessment of atrazine (Atz) transport in the subsurface environment". Magesan et al [20] suggestted that "atrazine (Atz) adsorption decreased with soil depth and was correlated with percentage clay content, total C, cation exchange capacityand surface area". Ling et al [21] investigated "the influence of dissolved organic matter (DOM) on the sorption of atrazine (Atz) in ten soils.…”
Section: Atrazine (Atz) Sorptionmentioning
confidence: 99%